KONTEKS PENGEMBANGAN EKONOMI–EKOLOGI MASYARAKAT(COMMUNITY ECONOMYANDECOLOGYDEVELOPMENT) KABUPATEN PIDIE JAYA - Nurjanah Nurjanah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
This research report has beenreviewing the context of economic development-ecological communitiesPidie Jaya. Seeing the condition of natural resource management, the problem lies in the managementof natural resources related to the economic and ecological basis Aceh alleged birthplace of armedconflict in the 1970's. Political and economic tensions in the former conflict and tsunami destroyed theeconomy and ecology of the Acehnese people, usually heats up along with the emergence of rivalrybetween the various political and economic power. Momentum Momentum Aceh peace and electionshave become the domain of the end of conflict and bring peace and the effects can be expected toaccelerate the development process of Aceh in the future. The focus of the problem lies in thecharacteristics (Community Economic Development) around the area of operations of the company. Inthis survey, the Economy-Ecology parameter that will be seen are: Livelihood patterns, level ofdependence on resources related to their livelihoods, access to economic capital and distribution,economic value of fishing for communities, Local Economic Infrastructure, Local Labour Force Figures ,Gini Ratio and Rural Poverty Level (Village level). Primary and secondary sources of data will be analyzedwith descriptive methods, qualitative and quantitative, Shape Activities: The process of recognition ofthe general characteristics of the Acehnese people and the communities that surround the region ofAceh Pidie, Pijay District, District Bireun and Sabang can be done in several ways including throughobservation / observation, intensive discussions (FGD, wawawancara) and through the study ofdocuments. Purposes, among others: Identifying structure-sekonomi social and ecological coastalcommunities, coastal communities identify vulnerabilities in the survey in the context of localcommunity life and home economics, mapping key stakeholders and their roles in the socio-economicdynamics and ecology, and to prepare and establish recommendation program for local coastalcommunities in the context of social and environmental responsibility. Law of the sea in Pidie Jaya doesnot act as a medium of conflict resolution. The need for mentoring and training roles including chiefmerevitalisai laot and customary law of the sea. The role of commander laot not only regulates maritimeregulations for fishermen, but also as a medium of socialization and social conflict resolution. The role ofmaid agencies also quite a supervisor. In addition it is also important to community participation inpolitics so as to avoid themselves from desruktif political behavior, and the importance of cooperativerelationships by regents Pidie quite legitimated.